Entrepreneurial Students' Achievement Motivation towards Academic Excellence - Mellasanti Ayuwardani; Rara Ririn Budi Utaminingtyas; Rustono, Rustono; Sri Eka Sadriatwati; Irin Mirrah Luthfia (Cita konsultindo, 2024)
The advancement and convenience of technology nowadays are utilized by students to pursue their business endeavors. Entrepreneurial students remain actively engaged in their studies while running their businesses. A strong motivation is essential for entrepreneurial students to fulfill their roles both as students and entrepreneurs. This study is an explanatory research involving entrepreneurial students from the Department of Business Administration at Polines, with a sample size of 34 respondents. The results of this research indicate that achievement motivation has a calculated t-value (6.670)>tabulated t-value (1.694) with a significance of 0.000<0.05 towards academic achievement. Hence, it can be concluded that achievement motivation has a positive and significant influence on the academic performance of entrepreneurial students in the Department of Business Administration at Polines. The adjusted R Square value of 0.569 implies that 56.9% of academic achievement is influenced by achievement motivation. These findings suggest that despite engaging in business or entrepreneurship, students maintain high levels of achievement motivation, thus preserving their academic performance.